Assessing Antimicrobial Prescribing Patterns and Antimicrobial Resistance in Dhi Qar Governorate Hospitals; A retrospective study. - Basma Zuheir Al-Metwali; Hasan A. Shubbar (Iraqi Journal of Pharmaceutical Sciences, 2025)
Antimicrobial resistance (AMR) is a global concern, especially in low- and middle-income countries, threatening food production, healthcare, and life expectancy. Antimicrobial stewardship (AMS) programs can optimize antibiotic use, improve patient outcomes, lower AMR, and save healthcare costs. This observational-retrospective study in Dhi Qar Governorate aimed to assess antimicrobial prescribing patterns in Al-Nasiriya public hospitals. Dhi Qar Health Directorate comprises ten hospitals, and only one hospital was excluded from the study. The study used data from antibiotic stewardship committees, including antibiogram, antibiotic, and meropenem surveys, hospital pharmacies’ medical files, and the directorate statistics from 1/1/2023 to 1/10/2023. The number of patients undergoing antibiotic screening was 6090. Most patients (43.34%) were in the 18–49 years age range. Most cases of antibiotics' clinical indication were surgical procedures (41.82%), with cesarean sections being the most common (16.15%), followed by medical treatment (37.25%), with respiratory conditions (21.34%) being the most common. Most patients (99.72%) received empirical rather than targeted treatment, parenteral rather than oral treatment (98.93% were given parenteral antibiotics); more than half of patients (52.84%) were prescribed a combination of two or more antibiotics. Most cases (95.43%) in antibiotic screening were continued on the same dose without reviewing the antibiotic prescription after 48–72 hours. The treatment resulted in 87.75% healing, 53.57% discharge with antibiotic discontinuation, and a 1.21% death rate among patients. Metronidazole, ceftriaxone, meropenem, amoxicillin, and cefotaxime were the most frequently prescribed antibiotics. The data from hospital pharmacies’ medical files showed the consumption of 14 types of antibiotics within the WHO's Watch group and 18 within the Access group. The most antibiogram-isolated bacteria were E. coli (19.06%), Staphylococcus non-aureus spp. (18.74%), Staphylococcus aureus (11.26%), Klebsiella pneumonia (10.15%), and Pseudomonas aeruginosa (7.88%). The antibiogram showed resistance to many antibiotics, and there was a significant difference in resistance distribution among the Access, Watch, and Reserve groups (P value = 0.024). Antibiotic practice showed empirical treatment with broad-spectrum antibiotics (most of which are in the WHO Watch group), limited culture and sensitivity testing, and limited antibiogram use, making monitoring antibiotic resistance hard.